The role of the courts in conflict resolution in UK flood risk management - Khizar Khalil; Edmund C. Penning‐Rowsell (Journal of Flood Risk Management, 2023)
Abstract Conflicting interests in flood risk management (FRM) frequently arise, resulting in disputes which are often resolved through mutual agreement. Nevertheless, a small number of cases require legal intervention when negotiation or mediation fails. This can publicly reveal the conflict often hidden in these mutual agreements. The two areas that intersect to create this conflict are spatial planning and flood risk reduction strategies that may impact property rights. This research explores the nature of such conflict in FRM and its possible resolution. Through an analysis of 25 all‐UK legal Court transcripts, we investigate the underlying flood‐related disputation, dispute types, and how they were resolved. Our findings reveal that certain disputes remain unresolved prior to Court proceedings due to misunderstandings about spatial planning in at‐risk areas. In addition, the depiction and the accuracy of flood risk assessments can be a contentious issue. Some FRM disputes remain irresolvable due to the differences in collective and individual aspirations about the use of land by various interests: developers, local authorities, residents, landowners, and farmers. Understanding these FRM disputes and their judicial resolution is valuable in unambiguously revealing who are the ultimate ‘winners’ and ‘losers’ in these fiercely contested struggles.